Pulsewidth limitation in the relativistic backward wave oscillator; IEEE Transactions on Plasma Science; Vol. 28, iss. 3 - Korovin S. D. Sergei Dmitrievich; Mesyats G. A. Gennady Andreyevich; Pegel I. V. Igor Valerievich; Polevin S. D.; Tarakanov V. P. Vladimir Pavlovich (2000, 2000)
Title screen